PENGARUH KEKERASAN VERBAL DALAM RUMAH TANGGA TERHADAP KEPERCAYAAN DIRI DAN HARGA DIRI PASANGAN - Nurhidayati Nurhidayati (Pelantar Press, 2025)
This article aims to determine the effect of verbal violence on the self-confidence and self-image of couples. The data analysis technique uses simple linear. Based on the results of the Simple Linear analysis test, it shows that there is a significant influence between Verbal Violence (X) on Self-Confidence (Y1) with a regression coefficient value of 0.955, there is a significant influence between Verbal Violence (X) on Self-Image (Y2) with a regression coefficient value of 1.241. The trust and confidence of couples decreases along with the level of verbal violence. Lack of self-confidence caused by verbal violence from a partner gives rise to self-doubt. Those who engage in verbal abuse often distort facts to make the victim doubt their memories, perceptions, and even their own sanity. Individuals who frequently experience verbal violence will also try to avoid their anger or criticism from their partners, and victims will learn to remain silent. He will suppress his own desires, opinions and feelings. The victim will lose their voice and identity as a result. It is possible that negative self-image is internalized as part of self-confidence. The victim will have a bad body image or self-image if the partner continues to emphasize their physical, intellectual or character deficiencies. Mental health problems such as anxiety and prolonged stress can be caused by verbal violence. This can also cause victims to lose their self-identity or develop a negative self-identity